Implementation Of B2B E-Commerce System: A Case Study In Small And Medium Industry (SMI) - Geeng, Lai Jin (2002)
Hallmark Product Sdn Bhd, a small medium manufacturing and retailing of food and beverage company has been selected as the study target. Other than the case study the author also developed an e-commerce system prototype to further support the study.